Recomendaciones para el diseño de circuitos impresos de potencia - López Sánchez, Jaime; Rojas Salamanca, Fernando Antonio; Trujillo Rodríguez, César Leonardo; Guacaneme Moreno, Javier Antonio (Ingeniería, 2003)
Commonly you can see that many of PCB designers (Printed Circuit Board) when generating a power's printed circuit, they don't consider factors like the disposition of the elements, ground's references,components DC and AC of operating signals or dimension of traces. These considerations could be entail phenomena like electromagnetic interference (EMI), instability and reduction of life's time of circuit.In the present paper are mentioned some recommendations for the right design of power's PCB